Evaluating the Role of Monetary Policy Tools in Stimulating Domestic Savings In Egypt During the Period 1990-2014 - Ahmed , Sakr; Al-Sayed, Waffa; Fahmy, Nesrin (The Arab Journal of Administration, 2021)
This paper presented a comprehensive econometric analysis of the determinants of decrecing the rates of the domestic savings in Egypt during the study period (1990-2014). The analysis helped to determine the relative contributions of the monetary policy tools in this regard. The main results confirmed that: existence of co-integration between variables refred to a balanced relationship in the long term. So, about 91% of the changes in the domestic savings were achieved through out changes of the monetary variables (when the other factors were conctant).